Physician-Perceived Challenges in End of Life Care - Stumpf, Carina (Université d'Ottawa / University of Ottawa, 2019)
Background: Multiple factors influence end of life care and can lead to barriers in the experience of care for patients and the delivery of care for physicians. It is vital to determine the possible challenges physicians may face in providing end of life care in order to understand and decrease these challenges. Objective: The purpose of this study was to identify and understand the different challenges physicians face in the provision of quality end of life care. Methods: First, a scoping review was conducted on five databases to gather knowledge on the current literature on physician-perceived challenges in end of life care. Subsequently, a secondary data analysis was performed from the results of a pan-Canadian study with 1 060 respondents on medical end of life practices to: (1) measure the frequency of physician-perceived challenges based on the last patient who died under their care in the last 12 months, and (2) assess the relationship between the challenges and the physician’s or patient’s sociodemographic characteristics. Results: The results of the scoping review on 40 studies identified ten challenges: physician’s characteristics, family issues, team conflicts, team and family conflicts, institutional and organizational factors, training and educational factors, religious challenges, ethnicity and value-related challenges, human rights issues, and language challenges. Results from the secondary data analysis revealed that 26.9% of physicians reported at least one challenge, such as family conflicts, in the provision of end of life care with the last patient who died under their care in the last 12 months. Conclusion: These challenges restrict quality end of life care. As such, targeted strategies should be implemented to mitigate these barriers to end of life care and improve care.
Keywords: Physician; End of Life; Health Sciences; Challenges